Genetic Foundation of Prostaglandin Metabolism Influences Patent Ductus Arteriosus Closure in Extremely Low Birth Weight Infants - Sampath, Hannah J.; Krishnan, Parvathy; Trinh, Van; Parton, Lance A. (American Journal of Perinatology, 2024)
Objective Prostaglandins (PGs) play a major role in maintaining patency of the ductal arteriosus (DA). Pulmonary 15-hydroxyprostaglandin dehydrogenase (PGDH), which is ecoded by the hydroxyprostaglandin dehydrogenase (HPGD) gene, is the primary enzyme responsible for PG breakdown. Animal studies have shown HPGD-knockout mice have significantly higher prostaglandin E2 levels and no ductal remodeling. Functional variants of the HPGD gene that alter PG breakdown have not been studied in preterm infants with patent ductus arteriosus (PDA).Study Design This was an observational cohort study including extreme low birth weight (ELBW) infants classified as having spontaneous, medical, or procedural (transcatheter or surgical ligation) closure of their DA. Urine prostaglandin E metabolite (PGEM) levels were measured in ELBW infants following ibuprofen treatment using competitive ELISA. HPGD genetic variants rs8752, rs2612656, and rs9312555 were analyzed. Kruskal–Wallis, Fisher's exact, chi square, logistic regression, and Wilcoxon signed-rank tests were used; p < 0.05 was considered significant.Results Infants in the procedural closure group had a younger gestational age (GA). The incidence of spontaneous closure or medical closure was higher compared to procedural closure in the presence of any minor allele of rs8752 (67 and 27%, respectively; p = 0.01), when adjusted for GA and gender. Haplotype analysis of three variants of HPGD revealed differences when comparing the spontaneous and medical closure group to the procedural group (p < 0.05). Urinary PGEM levels dropped significantly in those ELBW infants who responded to ibuprofen (p = 0.003) in contrast to those who did not respond (p = 0.5).Conclusion There was a different genotype distribution for the rs8752 genetic variant of the HPGD gene—as it relates to the mode of treatment for ELBW infants with PDA. We speculate that medical management in the presence of this variant facilitated additional PG breakdown, significantly abrogating the need for procedural closure. Additionally, differences in genotype and haplotype distributions implicate a specific HPGD genetic foundation for DA closure in ELBW infants.Key Points
Keywords: single nucleotide polymorphism; preterm infant; patent ductus arteriosus; prostaglandin dehydrogenase; neonatology